Principles of genetics - Snustad, D. Peter; Snustad, D. Peter; Simmons, Michael J (United State, Wiley, 2019)
Principles of Genetics is one of the most popular texts in use for the introductory course. It opens a window on the rapidly advancing science of genetics by showing exactly how genetics is done. Throughout, the authors incorporate a human emphasis and highlight the role of geneticists to keep students interested and motivated. The seventh edition has been completely updated to reflect the latest developments in the field of genetics. Principles of Genetics continues to educate today$1 (Bs students for tomorrows science by focusing on features that aid in content comprehension and application. This text is an unbound, three hole punched version.s
Glossary 584-606p. ; Index 607-627p.
Keywords: Extensions of mendelism; Genomics; The science of genetics; Translation and the genetic; Zoology; Genetic Phenomena